Optical coherence tomography angiography monitors human cutaneous wound healing over time - Deegan, Anthony J.; Wang, Wendy; Men, Shaojie; Li, Yuandong; Song, Shaozhen; Xu, Jingjiang; Wang, Ruikang K. (Quantitative Imaging in Medicine and Surgery; Vol 8, No 2 (March 28, 2018): Quantitative Imaging in Medicine and Surgery, 2018)
Background: In vivo imaging of the complex cascade of events known to be pivotal elements in the healing of cutaneous wounds is a difficult but essential task. Current techniques are highly invasive, or lack the level of vascular and structural detail required for accurate evaluation, monitoring and treatment. We aimed to use an advanced optical coherence tomography (OCT)-based angiography (OCTA) technique for the non-invasive, high resolution imaging of cutaneous wound healing. Methods: We used a clinical prototype OCTA to image, identify and track key vascular and structural adaptations known to occur throughout the healing process. Specific vascular parameters, such as diameter and density, were measured to aid our interpretations under a spatiotemporal framework. Results: We identified multiple distinct, yet overlapping stages, hemostasis, inflammation, proliferation, and remodeling, and demonstrated the detailed vascularization and anatomical attributes underlying the multifactorial processes of dermatologic wound healing. Conclusions: OCTA provides an opportunity to both qualitatively and quantitatively assess the vascular response to acute cutaneous damage and in the future, may help to ascertain wound severity and possible healing outcomes; thus, enabling more effective treatment options.